'Help! I have been Gong Tao-ed!' Exploring discourses surrounding siam diu culture in Singapore - Goh, Dominic Kai Xiang (Nanyang Technological University, 2020)
Discourse is a powerful way of looking at how social practices are represented. Using multimodal critical discourse analysis, I uncover the discourses surrounding Thai disco culture in Singapore. Thai discos are known as siam dius and its culture is characterized by the practice of tipping the Thai women who work there via hanging flower garlands. These discourses also help to tell us how stereotypes of people in siam dius are represented online. Data was collected from a Facebook page called Gong Tao Help Desk. The results reveal two main discourses. The first is about language and communication. The second is about language and sexuality. Through these discourses, the stereotypical Singaporean man in a siam diu is represented as being communicatively competent in Thai. The stereotypical Thai woman is a hypersexualized bimbo who uses simple phrases to extract money from her customers.